(untitled) (Research, Society and Development, 2024)
Auxetic materials are those that have a negative Poisson’s ratio, that is, they expand when pulled, unlike conventional materials. They have superior mechanical characteristics than conventional ones, such as resistance to impact and fracture, shear and indentation, in addition to being vibration and noise attenuators. Such characteristics are due to its complex structure. In this sense, the article aims to explore the physical properties of these materials, as well as their current and potential applications in product design with the aim of improving their performance and functionality. Based on a literature review, the main mechanical properties, types of auxetic materials and applications of these materials in design, in the areas of fashion, aerospace, biomedical, protection and furniture are discussed. Future application possibilities are adressed, as well as the main obstacles to its large-scale implementation. It is concluded that the use of auxetic materials in design contributes to greater functionality and versatility of products, but more research is needed to overcome technical obstacles, promoting greater use of their potential in the market.